Social and ethical ideas in the works Utezhan Nurgaliyev (Collection of Ballads «Last summer war») (Journal of Philosophy Culture and Political Science, 2018)
This article discusses the problems of life in the work Otezhan Nurgaliyev in terms of sociophilosophical, ethical and aesthetic basis. Considering the historical and philosophical relationship, ballads poet conceptualized taking into account features to find their place in history. Heritage and architectural style of the writer is characterized not only from the point of view of literary criticism, but also show him aware of the traditions of the Kazakh philosophy and art, that writing team is trying to justify arguments. Raised in the collection of ballads thinker «Last summer war» socio-ethical, philosophical and life problems, installation of the era characterized by skill of the writer. Course of study is based on the heritage of the poet follows a systematic approach – poems, autobiographical ballads and philosophy. However, in this study failed to substantiate the prevalence and importance of social and ethical issues in the work of the writer, thus integrally understand worldview thinker. Key words: Utezhan Nurgaliyev, literature, philosophy, ethics, aesthetics, happiness.